Communication Strategy of the National Police Organization in the Implementation of the "Madago Raya Police" Program in Handling Radicalism In Poso Regency - Herawati, Andi Febri; Ilyas, Ilyas (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The handling of radicalism in Poso Regency is carried out in the form of the implementation of the "Madago Raya Police" program which aims to minimize the re-entry of radicalism to former theorist prisoners. This research uses a qualitative approach to understand the communication strategy of the National Police in the implementation of the "Madago Raya Police" program as an effort to handle radicalism in Poso Regency. The data in this study were collected through in-depth interviews, field notes, namely observations, and document analysis. The selected informants are members of the National Police who are tasked with carrying out the "Madago Raya Police" program and former theorist prisoners, as well as sympathizers and stakeholders. The research location is in Poso Regency, Central Sulawesi Province.  The results of the study show that in handling radicalism, the communication strategy of the National Police organization in the implementation of the "Madago Raya Police" program is carried out in the form of delivering messages through  a door to door system which aims to establish relationships, know the needs and expectations and change the mindset of former terrorism inmates to be liberal and pluralist. The message conveyed to former prisoners of terrorism was designed first by members of the National Police as part of the work of Kamtibmas, which of course was agreed by all parties in the police organization and then sent the message implicitly with the aim of inviting former terrorism prisoners to be involved and responsible in maintaining order and security in the Poso Regency area